NEW DATA ON THE GEOLOGY OF ITURUP ISLAND (KURIL ISLAND ARC) - Vitukhin D.I.; Oreshkina T.V.; Pushcharovskii Yu.M.; Tsukanov N.V. (My University, 1996)
The geology of Iturup Island, which is the largest one in the Kuril island arc, has not yet been considered in any special publications. The island is marked by the occurrence of typical island-arc deposits of the middle Miocene-Pliocene age that show complicated facial variability. Based on the analysis of siliceous plankton assemblages (diatoms, radiolarians), the age of several formations distinguished in both the Iturup and Kunashir islands has been determined more accurately. Paleontologically dated levels of transgressive events correlative with similar levels in the Neogene section of the Karaginskii Island (eastern Kamchatka), the reference one in the Far East, have been defined.
Keywords: Miocene; Pliocene; Neogene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene; Кайнозой::Неоген::Плиоцен